PELATIHAN PEMBUATAN PAKAN TERNAK ALTERNATIF DAN MANAJEMEN USAHA TERNAK KAMBING - Rusdi Rusdi; Wahidul Basri (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2020)
The main thing in the process of raising goats so that they can get benefits quickly is regular feeding. Based on the pleasant experience of the goat breeders complaining about the difficulty of getting natural food during the dry season. Or if there is a compilation of rainy season food available, then the breeder will eat it in feeding the goats every day. To do this, there is now a modern and easy way to raise goats that is quite easy and profitable is that cattle use fermented feed so they do not look for food every day. This method is not yet known by many goat farmers in both villages and cities in the country including in partner villa villages namely Jorong Padang Ambacang Nagari Batu Balang will be able to bring benefits that are more optimal and easier in raising goats. Community service aims to provide konowledge and skill to partners or goat farmers in animal husbandry management and application of science and technology to produce animal feed by fermentation. Methods of Implementation of activities carried out by applying appropriate technology and improving business management. The appropriate tecnology application implementation scheme is a training program to make alternative/ artificial fermentation. While management improvement training is realized in the form of counseling and training. The results of this service have been able to increase community knowledge about goat breeders in the terms of livestock business management and animal feed manufacturing through fermentation.